Prebiotic Activity Score Of Breadfruit Resistant Starch (Artocarpus altilis), Breadfruit Flour, And Inulin during In-Vitro Fermentation By Pure Cultures (Lactobacillus Plantarum, And Bifidobacterium Bifidum) - Zarinah, Zakaria; Norshazila, Shahidan; Napisah, Hussin (2018)
The prebiotics activity score was a quantitative method to measure to which extent prebiotics (Breadfruit Resistant starch, Breadfruit flour and Inulin) to support the growth of L.plantarum and B.bifidum. The changes in growth after fermentation (0, 6, 12, 24, 48 and 72 h) of bacteria strains on prebiotics and glucose in relation to changes in Escherichia coli grown under same condition was used to determine prebiotics score. The fermentation of the different carbon sources (Breadfruit Resistant starch, Breadfruit flour and Inulin) by L.plantarum and B.bifidum produce short chain fatty acids that determined by changes of pH throughout 72 h of fermentation. The highest score (0.45) was obtained for L.plantarum that utilised breadfruit resistant starch after 12 h of fermentation time. However, the highest score (0.65) for B.bifidum also utilised breadfruit resistant starch as carbon sources after 48 h of fermentation. It was found that there was significant difference in pH changes for both strains. Greatest pH reduction for L.plantarum and B.bifidum for all samples after 6 h of fermentation. In conclusion, breadfruit resistant starch has potential as prebiotics as it meets the requirement as a prebiotic.